Investigating Plagiarism: The Form and The Motivation in Performing Plagiarism in High Education - S Sariffuddin; Khristiana Dwi Astuti; Riyan Arthur (Journal of Education and Learning (EduLearn), 2017)
The rapid development of information technology, especially the Internet is pointed out to be factor driving the student to practice plagiarism. Prevention efforts continue to be made both from government policies and stakeholder by creating software anti-plagiarism. However, in the reality the practice of plagiarism re-mains common and relatively more widespread. This practice continues to be varied, so that we need to up-date the information and findings through investigations plagiarism practices in student assign-ments. The method used was a mixed-method approach or mix of quantitative and quali-tative approaches. A quantitative approach was done by using software turnitin.com to scan for plagiarism indication of the level of student assignment in common. To study the behavior of plagiarism, the interview process was also done informally to students who commit high plagiarism. The results showed that the pattern of students’ plagiarism consists of five forms: sham paraphrasing, illicit paraphrasing, other plagiarism, copying verbatim and purloining. Illicit paraphrasing practices are a form of copy-paste literature review and did not pay attention to the bibliography. Besides, the practice of plagiarism is closely associated with low academic writing knowledge. Therefore, the practice of plagiarism should not only be viewed from the perspective of the academic violations, but also from the other perspectives.